The linkage between team communication, team motivation and search and rescue team performance - Azlyn Ahmad Zawawi; Norsyazwani Ab Halim; Nur Zafifa Kamarunzaman; Azita Ahmad Zawawi; Fatimah Wati Halim (SA Journal of Human Resource Management, 2023)
Orientation: This study examined the linkage between team communication, team motivation and search and rescue (SAR) team performance.